Application of the Discussion Method to Improve Science Learning Outcomes in Grade IV Students of MlS Al-Khoiriyah Palembang - Arnianti, Arnianti; Indraswati, Dyah (Journal of Learning Improvement and Lesson Study, 2023)
Most of the students learning outcomes in learning are still low. This study aims to improve student learning outcomes in science class IV MIS.AL-Khoiriyah Palembang. The research method used was classroom action research method used was classroom action research. The research procedures included: planning, implementing, reflecting. The results showed that the use of the discussion method could improve student learning in class IV MIS.Al- Khoriyah Palembang. This can be seen from the percentage student learning outcomes, cycle 1 that 64,24% and in cycle 2 the value of student learning completeness increased KKM 70 and learning be seen from the percentage student lerning outcomes, in cycle 1 that is 64,24% and in cycle 2 the value of student learning completeness increased and increased and learning completeness increased and reached KKM 70 and learning completeness increased to 85,71%.